2020
DOI: 10.24818/ea/2020/s14/1120
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Work Investment for the Accounting Profession in Romania at Time of Coronavirus Pandemic

Abstract: Heavy work investment in various domains of activity has not been sufficiently explored. This paper investigates how accounting professionals in Romania perceived different aspects related to the heavy work investment during the coronavirus pandemic. Professional accountants devote, by the nature of their job, many hours of work. In March 2020, unprecedented measures were taken in Romania in the context of the coronavirus pandemic. These include the obligation to work remotely where possible. The study' object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
4
0
2
Order By: Relevance
“…Embora essas estratégias sejam eficazes em curto prazo, as empresas precisam atentar à diversidade e ao aprendizado de longo prazo (ALVES et al, 2020). Mihai et al (2020) afirmam que o trabalho durante a pandemia gerou estresse e fadiga adicionais, mas teve influência positiva na relação trabalho-família e na produtividade, e que contadores profissionais se adaptaram rapidamente ao trabalho a distância. A percepção do trabalho dos respondentes nessa pesquisa foi influenciada pelas seguintes variáveis: idade dos respondentes, cidade onde trabalham, forma de exercício da profissão (empregado ou autônomo) e porte da empresa em que trabalham.…”
Section: Análise Dos Resultadosunclassified
“…Embora essas estratégias sejam eficazes em curto prazo, as empresas precisam atentar à diversidade e ao aprendizado de longo prazo (ALVES et al, 2020). Mihai et al (2020) afirmam que o trabalho durante a pandemia gerou estresse e fadiga adicionais, mas teve influência positiva na relação trabalho-família e na produtividade, e que contadores profissionais se adaptaram rapidamente ao trabalho a distância. A percepção do trabalho dos respondentes nessa pesquisa foi influenciada pelas seguintes variáveis: idade dos respondentes, cidade onde trabalham, forma de exercício da profissão (empregado ou autônomo) e porte da empresa em que trabalham.…”
Section: Análise Dos Resultadosunclassified
“…Additionally, of the 103 studies selected and published between 2018 and 2021 it was found that accounting and its professionals, were addressed in six articles and they are: 1) Lin and Hwang ( 2021 ) presented an empirical study (quantitative approach) on how accountants manage knowledge sharing, information management and the psychological factors associated with this in the pre-pandemic and pandemic periods, concluding that information management skills and perceived image have a positive association with knowledge sharing behaviour, while reciprocity and knowledge power loss do not play a relevant role in knowledge sharing intentions; also suggest that accountants need to be increasingly resilient; 2) Feeney and Pierce ( 2018 ) empirically demonstrated (qualitative approach) that accounting is an enabler of innovation and creativity; 3) Dechawatanapaisal ( 2020 ) obtained a sample of 1137 accountants (questionnaire) to develop a model to examine whether work significantly influences career satisfaction through job integration, where the results obtained showed that the direct relationship existing between job meaning and satisfaction are measured by integration; 4) Melnyk et al ( 2020 ) identified the current and future directions in the development of accounting; 5) Faituša et al ( 2020 ) evaluated accounting outsourcing in Latvia and Lithuania (inductive and deductive method) and identified the personal, professional and social characteristics of certified accountants; 6) Mihai et al ( 2020 ) investigated how the pandemic forced accountants to make a heavy investment in their work (workload), which generated stressful situations, but with a positive balance in the relationship with the family. In short, empirical studies on work stress in accounting professionals are minute, which opens space to argue that this is a fertile topic for research and to justify the essence of this study presented here as a starting point.…”
Section: Scientific Mappingmentioning
confidence: 99%
“…In this context, accounting professionals invest immensely in their daily work to fulfil their obligations in a timely manner (Mihai et al, 2020 ). It is then perceived that these professionals are a facilitating target for stress, which has been defined as an emotional, unpleasant experience that is associated with fear, dread, anxiety, irritation, annoyance, anger, sadness, and depression (Motowidlo et al, 1986 ); a psychosocial risk (Sidhu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, the accountants had to invest more in technology. However, thanks to the assistance delivered by the companies in providing communication platforms during the pandemic period, this problem was minimized (Mihai et al, 2020(Mihai et al, : 1136.…”
Section: Introductionmentioning
confidence: 99%